On-Farm Mitigation of Transmission of Tuberculosis from White-Tailed Deer to Cattle: Literature Review and Recommendations - W. David Walter; Charles W. Anderson; Rick Smith; Mike Vanderklok; James J. Averill; Kurt C. VerCauteren (Veterinary Medicine International)
The Animal Industry Division of the Michigan Department of Agriculture and Rural Development (MDARD) has been challenged with assisting farmers with modifying farm practices to reduce potential for exposure to Mycobacterium bovis from wildlife to cattle. The MDARD recommendations for on-farm risk mitigation practices were developed from experiences in the US, UK and Ireland and a review of the scientific literature. The objectives of our study were to review the present state of knowledge on M. bovis excretion, transmission, and survival in the environment and the interactions of wildlife and cattle with the intention of determining if the current recommendations by MDARD on farm practices are adequate and to identify additional changes to farm practices that may help to mitigate the risk of transmission. This review will provide agencies with a comprehensive summary of the scientific literature on mitigation of disease transmission between wildlife and cattle and to identify lacunae in published research.